2019
DOI: 10.3390/cancers11101556
|View full text |Cite
|
Sign up to set email alerts
|

Topical 2′-Hydroxyflavanone for Cutaneous Melanoma

Abstract: 2′-hydroxyflavanone (2HF) is a dietary flavonoid with anticancer activity towards multiple cancers. Here, we report that topically applied 2HF inhibits the growth of intradermal implants of melanoma in immunocompetent mice. 2HF induced apoptosis and inhibited the growth of the human SK-MEL-24 as well as murine B16-F0 and B16-F10 melanoma cell lines in vitro. Apoptosis was associated with depletion of caspase-3, caspase-9, and PARP1 in B16-F0 and SK-MEL-24 cells. Caspase-9 and MEKK-15 were undetected even in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 68 publications
(110 reference statements)
3
21
0
Order By: Relevance
“…Results demonstrated that the fluorescence was distributed throughout the cytoplasm of control antisense (CAS) or vehicle-treated cells, whereas in cells transfected with Rlip-LNA, the rhodamine signal remained localized near the plasma membrane ( Figure 5 B) as we showed previously [ 58 ]. The inhibitory effects of Rlip-LNA on endocytosis were also similar to those observed previously by depletion of Rlip by the R508 antisense and were consistent with previous studies showing that the endocytic process is interrupted soon after internalization, leaving vesicles stalled along the plasma membrane [ 38 , 58 ]. In conclusion, our results demonstrated that inhibition of EGF endocytosis and induction of apoptosis by Rlip depletion are possible mechanisms of anticancer effects in the human breast cancer cell lines MCF7 and MDA-MB-231.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Results demonstrated that the fluorescence was distributed throughout the cytoplasm of control antisense (CAS) or vehicle-treated cells, whereas in cells transfected with Rlip-LNA, the rhodamine signal remained localized near the plasma membrane ( Figure 5 B) as we showed previously [ 58 ]. The inhibitory effects of Rlip-LNA on endocytosis were also similar to those observed previously by depletion of Rlip by the R508 antisense and were consistent with previous studies showing that the endocytic process is interrupted soon after internalization, leaving vesicles stalled along the plasma membrane [ 38 , 58 ]. In conclusion, our results demonstrated that inhibition of EGF endocytosis and induction of apoptosis by Rlip depletion are possible mechanisms of anticancer effects in the human breast cancer cell lines MCF7 and MDA-MB-231.…”
Section: Resultssupporting
confidence: 80%
“…We previously demonstrated that the rate of GS-E efflux by Rlip mutants correlates directly with its anti-apoptotic activity and with the rate of endocytosis of EGF and insulin [ 34 ]. We recently observed that depletion of Rlip protein also inhibits CDE in melanoma and lung cancer [ 58 , 59 ]. To determine whether LNA-mediated depletion of Rlip is also relevant in inhibition of CDE in breast cancer cells, we investigated the effect of Rlip depletion by antisense on the endocytosis of EGF-rhodamine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In stark contrast, mice lacking the RALBP1 ((RalA Binding Protein 1) gene, which encodes RLIP76 (also known as Rlip (RALBP1), used here for both gene and protein), a stress-responsive, anti-apoptotic protein, are highly resistant to carcinogenesis by even the most potent chemical carcinogens [ 10 ]. Targeted inhibition or depletion of RALBP1 causes regression of many types of cancer [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In studies to examine the effect of combined RALBP1 and TP53 deficiency, we discovered that hemizygous RALBP1 deficiency was sufficient to exert a strong dominant negative effect on the spontaneous carcinogenesis phenotype of homozygous TP53-null mice [ 10 ].…”
mentioning
confidence: 99%